Analisis Penerapan SOP Dalam Pengendalian NRW (Non Revenue Water) Pada Perumdam Tirta Tarum Kabupaten Karawang Cabang Kotabaru - Prastiwi, Egis; Masduqi, Ali; Sundoro, Muhammad (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Perumdam Tirta Tarum Karawang Regency, an agency providing drinking water services with service coverage for a population of 22.58%, has an NRW (Non-Revenue Water) level of 32.16%  and the NRW level for the Kotabaru Branch service area is 29.21%  in 2022. Analysis of the implementation of SOPs (standard operating procedures) in NRW control needs to be carried out so that monitoring of quality consistency can be carried out and makes it easier to evaluate the implementation of NRW control activities that have been carried out. This research uses quantitative and qualitative methods by conducting observations and interviews with related parties that focus on 7 (seven) indicators in the SOP: efficiency, consistency, error minimization, problem-solving, workforce protection, work maps, and defense boundaries. The results of the analysis carried out on the implementation of SOPs at Perumdam Tirta Tarum Karawang Regency related to 7 (seven) SOP indicators showed that the effectiveness of the performance of 5 (five) SOP indicators was good, while 2 (two) SOP indicators were still in the sufficient category. Overall, the implementation of existing SOPs is easy to understand and has been implemented well. However, if you look at the details of this reference SOP, it is still passive NRW control. The implementation of the SOP can only be carried out after receiving reports and complaints from the public.  Keywords: SOP (standard operating procedures), NRW, Perumdam Tirta Tarum.  Abstrak  Perumdam Tirta Tarum Kabupaten Karawang sebagai instansi penyedia jasa air minum dengan cakupan pelayanan terhadap jumlah penduduk sebesar 22,58 % memiliki tingkat NRW (Non Revenue Water) sebesar 32,16 % dan tingkat NRW untuk wilayah pelayanan Cabang Kotabaru sebesar 29,21 % pada Tahun 2022 Analisis penerapan SOP (standar operasional prosedur) dalam pengendalian NRW perlu dilakukan agar pemantauan terhadap kosistensi kualitas dapat dilakukan dan memberikan kemudahan dalam mengevaluasi pelaksanaan kegiatan pengendalian NRW yang telah dilakukan. Penelitian ini menggunakan metode kuantitatif dan kualitatif dengan melakukan observasi dan wawancara dengan pihak-pihak terkait yang difokuskan pada 7 (tujuh) indikator dalam SOP yaitu efisiensi, kosistensi, minimalisasi kesalahan, penyelesaian masalah, perlidungan tenaga kerja, peta kerja, dan batasan pertahanan . Hasil analisis yang   dilakukan terhadap penerapan SOP pada Perumdam Tirta Tarum Kabupaten Karawang dikaitkan dengan 7 (tujuh) indikator SOP didapatkan hasil bahwa penerapan 5 (lima) indikator SOP secara efektifitas sudah baik., sedangkan 2 (dua) indikator SOP masih masuk dalam kategori cukup. Sehingga secara keseluruhan penerapan SOP yang sudah ada mudah dipahami dan sudah diterapkan dengan baik, namun jika dilihat dari detail SOP acuan ini masih bersifat pengendalian NRW secara pasif, penerapan SOP baru dapat dilakukan setelah mendapat pelaporan, aduan dari masyarakat.